Understanding Moral Psychology in Context: Emotions, Reasoning, and Social Norms - Mudzakkir (Indonesian Scientific Publication, 2024)
This narrative review explores the psychological foundations of moral decision-making and prosocial behavior by examining the roles of emotion, reasoning, and contextual factors. The objective is to synthesize recent empirical findings to understand how these dimensions interact to influence moral actions. A systematic literature search was conducted using databases such as Scopus, PubMed, and Google Scholar, with keywords including